Integration of Religion and Science in the Quran: Interpretation of Surah Ar-Rahman Verses 19-20 in Tafsir An-Nur Hasby Ash-Shiddiqy - Samhudi, Samhudi; Ibrahim, Muhammad Syahrial Razali (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
This study aims to discuss the integration of religion and science in the interpretation of Surah Ar-Rahman verses 19-20 in Tafsir An-Nur by Hasby Ash-Shiddiqy. The research focuses on the interpretation of surah Ar-Rahman verses 19-20, analysis of the integration of religion and science in the context of the verse, and the implications of the integration of religion and science for the development of Islamic education and science. This research uses the maudhui tafsir research method. The results showed that Hasby Ash-Shiddiqy interpreted the two seas in Surah Ar-Rahman verses 19-20 as two different types of water, namely fresh water and salt water. Although the two meet in several places such as the mouth of the river that meets the sea, they do not mix completely. This phenomenon is explained as the existence of a boundary or separating the two waters. The integration between religion and science in this tafsir also has an impact on the development of Islamic education and science. In Islamic education, this integration provides an alternative holistic approach in the teaching and learning process and has an impact on the character building of Muslim scientists and the development of multidisciplinary research. In addition, the integration of religion and science in this tafsir has implications for the development of science, including in shaping the ethics of technological development and producing science that has a positive social impact.